THE CONCEPT OF FORGIVENESS IN THE QUR’AN: A QUR’ANIC APPROACH TO MENTAL HEALTH - Nasrulloh, Emha Hasan; Mas'ud, Marwan; Harsaputra, Taqy Kanz (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
Purpose: This study examines the concept of forgiveness in the Qur’an by integrating semantic, normative, and psychosocial perspectives, with the aim of clarifying its role in character formation and mental well-being. Methodology: Using a qualitative library-based approach, the study analyzes Qur’anic verses, Prophetic hadith, and classical as well as contemporary exegesis through linguistic–semantic, comparative exegetical, and normative–ethical analysis. Findings: The Qur’an presents forgiveness as a hierarchical ethical system comprising al-‘afw (relinquishing retaliation), aṣ-ṣafḥ (inner magnanimity), and al-maghfirah (moral and social protection). Forgiveness is positioned as a higher moral choice beyond justice, contributing to tazkiyat al-nafs, emotional regulation, mental tranquility, and the formation of Qur’anic character. Research Implication: The findings provide an integrative ethical framework applicable to Islamic character education, conflict resolution, and mental health discourse. Originality: This study offers a holistic Qur’anic model of forgiveness by systematically integrating theological, ethical, and psychospiritual dimensions within a single analytical framework.